Conservative finite-volume framework and pressure-based algorithm for flows of incompressible, ideal-gas and real-gas fluids at all speeds - Denner, Fabian; Evrard, Fabien; van Wachem, Berend G.M. (Journal of computational physics, 2020)
A conservative finite-volume framework, based on a collocated variable arrangement, for the simulation of flows at all speeds, applicable to incompressible, ideal-gas and real-gas fluids is proposed in conjunction with a fully-coupled pressure-based algorithm. The applied conservative discretisation and implementation of the governing conservation laws as well as the definition of the fluxes using a momentum-weighted interpolation are identical for incompressible and compressible fluids, and are suitable for complex geometries represented by unstructured meshes. Incompressible fluids are described by predefined constant fluid properties, while the properties of compressible fluids are described by the Noble-Abel-stiffened-gas model, with the definitions of density and specific static enthalpy of both incompressible and compressible fluids combined in a unified thermodynamic closure model. The discretised governing conservation laws are solved in a single linear system of equations for pressure, velocity and temperature. Together, the conservative finite-volume discretisation, the unified thermodynamic closure model and the pressure-based algorithm yield a conceptually simple, but versatile, numerical framework. The proposed numerical framework is validated thoroughly using a broad variety of test-cases, with Mach numbers ranging from 0 to 239, including viscous flows of incompressible fluids as well as the propagation of acoustic waves and transiently evolving supersonic flows with shock waves in ideal-gas and real-gas fluids. These results demonstrate the accuracy, robustness and the convergence, as well as the conservation of mass and energy, of the numerical framework for flows of incompressible and compressible fluids at all speeds, on structured and unstructured meshes. In particular, the precise recovery of a divergence-free velocity field in the incompressible limit, the accurate prediction of acoustic waves, and the convergence to the correct weak solution for strong shock waves with the same finite-volume discretisation and pressure-based algorithm are important features of the proposed numerical framework. •Fully-coupled pressure-based algorithm for flows at all speeds.•Identical finite-volume discretisation for incompressible and compressible fluids.•Unified thermodynamic closure model for incompressible, ideal-gas und real-gas fluids.•Precise recovery of a divergence-free velocity field for incompressible flows.•Convergence to the correct weak solution for strong shock waves.